Cross-border Tertiary Education : A Way towards Capacity Development - OECD; World Bank (Paris: OECD, 2012)
This report emphasizes that cross-border tertiary education refers to the movement of people, programs, providers, curricula, projects, research and services in tertiary (or higher) education across national jurisdictional borders. Cross-border education is a subset of educational internationalization and can be part of development cooperation projects, academic exchange programs and commercial initiatives. The focus of this volume is on the mobility of students, programs and providers/institutions. Student mobility remains relatively small, but has grown at an unprecedented pace in the past decade. The study concludes that cross-border tertiary education can be a helpful capacity development tool that countries and donor countries and agencies should consider in their development strategies. Finally, with the growth of trade in education services and the inclusion of the sector in the General Agreement on Trade in Services (GATS), countries and their education community should develop a better technical understanding of trade agreements. These agreements can be a tool in their capacity-building strategy, but the consequences and uncertainties of making certain commitments should be well understood. Whatever development strategy they chose, countries should consider whether cross-border tertiary education should be part of it, and if yes, how.